Perspectives of Mediation as a Consensual Dispute Resolution Tool under the Convention on the Civil Aspects of International Child Abduction - A. P. Klementiev; A. A. Ilkevich (Теоретическая и прикладная юриспруденция)
The article is devoted to mediation as consensual method of dispute resolution within the framework of the 1980 Hague Child Abduction Convention. The authors justify the advantages of mediation with a view to secure the best interests of a child. In particular, mediation may facilitate more expedited return of a child when compared to court procedures as well as exert a positive impact on its emotional status. Although mediation itself is not mentioned in the convention, Hague Conference on Private International Law managed to fill the said gap by the publication of the mediation guide applicable to cross-border transfer and retention of children. Apart from the analysis of the guide, authors provide examples of court rulings involving international disputes and illustrating the attempts to introduce mediation into international child abduction cases at the initiative of the court or central authority as well the parents of the removed or retained child. Unfortunately, such attempts prove to be unsuccessful in the overwhelming majority of cases, therefore the work aimed at implementation of mediation into such disputes should be intensified.